Germ Patterns And Pattern Resistance Against BacteriaAntibiotics In Patients Tract Infection Breathing Acute ( Ispa ) In Hospital PKU Muhammadiyah Surakarta Month January - March 2016 - Aji Kusuma, Bagas; , Prof. Dr. M. Kuswandi, SU., M.Phil., Apt; , Maryati, Ph.D., Apt (2016)
Acute Respiratory Infections (ARI) is a disease that commonly occurred in types of society. In many developing countries, more than 50% of deaths are caused by acute respiratory infections. This research was conducted to obtain data on bacterial resistance patterns to antibiotics in patients with ARI at PKU Muhammadiyah Hospital in Surakarta from January to March 2016 that can be used as consideration in the selection of antibiotic therapy in patients with ARI. Non-experimental descriptive method is used in this research as well as using 11 isolates from 11 patients who have failed in empirical antibiotic therapy. The results showed that the bacterium Enterobacter cloacae 100% (3 patients) were resistant to the antibiotic cefotaxime, amoxicillin, and 66.6% (2 patients) were resistant to cetazidim and moxifloxacin. Staphylococcus aureus 100% (2 patients) were resistant to trimetropim, cefotaxime, ciprofloxacin, tetracycline, erythromycin, amoxicillin, ceftazidim, moxifloxacin and 50% (1 patient) were resistant to levofloxacin. Pseudomonas aeruginosa 100% (2 patients) were resistant to trimethoprim, tetracycline, erythromycin, amoxicillin, ceftazidim. The antibiotics ciprofloxacin and moxifloxacin show resistance by 50% (1 patient). Streptococcus sp. resistant to cefotaxime, tetracycline, erythromycin, amoxicillin, ceftazidim. Chromobacterium violaceum bacteria resistant to trimethoprim, tetracycline, erythromycin, amoxicillin, moxifloxacin. Klebsiella pneumoniae bacteria resistant to trimethoprim, cefotaxime, ciprofloxacin, tetracycline, erythromycin, amoxicillin, ceftazidim, moxifloxacin. Then for Pseudomonas oryzihabitans bacteria was resistant to levofloxacin, trimethoprim, ciprofloxacin, tetracycline, erythromycin, amoxicillin, ceftazidim and moxifloxacin.